2021
DOI: 10.1111/mmi.14861
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evolution of initiation factor 3 and the ribosomal protein uS12 optimizes Escherichia coli growth with an unconventional initiator tRNA

Abstract: The anticodon stem of initiator tRNA (i‐tRNA) possesses the characteristic three consecutive GC base pairs (G29:C41, G30:C40, and G31:C39 abbreviated as GC/GC/GC or 3GC pairs) crucial to commencing translation. To understand the importance of this highly conserved element, we isolated two fast‐growing suppressors of Escherichia coli sustained solely on an unconventional i‐tRNA (i‐tRNAcg/GC/cg) having cg/GC/cg sequence instead of the conventional GC/GC/GC. Both suppressors have the common mutation of V93A in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…IF3 is known to play a role in discriminating against the tRNAs not having 3GC base pairs ( 18 ). Recently, we have also reported a mutation (V93A) is necessary in IF3 to allow initiation with a non-3GC i-tRNA ( 46 ). Although there is no direct interaction between IF3 and 3GC base pairs, this discrimination is most likely modulated through the interaction of 3GC base pairs with G1338 and A1339 of the 16S rRNA during i-tRNA accommodation ( 17 ).…”
Section: Discussionmentioning
confidence: 97%
“…IF3 is known to play a role in discriminating against the tRNAs not having 3GC base pairs ( 18 ). Recently, we have also reported a mutation (V93A) is necessary in IF3 to allow initiation with a non-3GC i-tRNA ( 46 ). Although there is no direct interaction between IF3 and 3GC base pairs, this discrimination is most likely modulated through the interaction of 3GC base pairs with G1338 and A1339 of the 16S rRNA during i-tRNA accommodation ( 17 ).…”
Section: Discussionmentioning
confidence: 97%
“…Ribosomal protein S12 has been intimately linked to ribosomal fidelity since the classical studies in bacteria of GORINI and KATAJA (1964). More recent work uncovered the existence of a large number of fidelity mutations, sparsely distributed throughout the primary sequence of bacterial S12 (Gregory et al, 2001;Agarwal et al, 2011;Datta et al, 2021). The high structural homology existing between E. coli S12 and MRPS12/ uS12m (Figure 2A, and Figure 2 in Vila-Sanjurjo et al, 2023) permits the extrapolation to mitochondria of the general conclusions regarding the involvement of MRPS12/uS12m in mito-ribosomal fidelity obtained in heterologous systems.…”
Section: Discussionmentioning
confidence: 99%
“…(A) Alignment between the E. coli and human mitochondrial versions of ribosomal protein S12. Sites of S12 fidelity mutations are color coded as indicated in color key above the alignment (Gregory et al, 2001;Agarwal et al, 2011;Datta et al, 2021). Note that the bacterial numbering is offset by one residue relative to the aforementioned references due to the inclusion of an M at position 1. the single-stranded stretch linking h3 and the functionally important central pseudoknot (helices h1 and h2) to h19 (Supplementary Figure S1A) (Brink et al, 1993;Poot et al, 1996;Poot et al, 1998).…”
Section: Figurementioning
confidence: 99%
“…Translational fidelity and pep-tRNA drop-off were implicated by genetic studies 44 , 84 , 96 . More recently, the mutants of uS12, a ribosomal protein involved in the decoding accuracy, have been reported to have genetic interactions with RRF and PTH 97 , 98 . An earlier study showed that streptomycin, a miscoding-inducing antibiotic, increased pep-tRNA drop-off and the temperature sensitivity of pth ts strain and expected the preferential dissociation of erroneous pep-tRNAs from ribosome 99 .…”
Section: Discussionmentioning
confidence: 99%